Assessment of the 2016/17 Food Insecurity Response Programme in Malawi - Babu, Suresh Chandra; Comstock, Andrew R.; Baulch, Bob; Gondwe, Anderson; Kazembe, Cynthia; Kalagho, Kenan; Aberman, Noora-Lisa; Fang, Peixun; Mgemezulu, Overtoun Placido; Benson, Todd (International Food Policy Research Institute, 2018)
Following poor harvests in the 2015/16 cropping season in Malawi, vulnerability assessments found that nearly 6.7 million people, primarily in the Southern and Central regions, were likely to suffer from food insecurity before the next harvest. The government of Malawi and its development partners designed the 2016/17 Food Insecurity Response Programme (FIRP) in Malawi to meet the food needs of many of the households affected, mobilizing approximately USD 265 million in resources to do so. In the wake of this intervention, a team led by the International Food Policy Research Institute was contracted to assess the quality of this humanitarian response along four primary dimension: Assess the quality of the national food security assessments which began the response; Investigate the accuracy of the geographical and beneficiary targeting within selected areas; conduct an operational assessment of the humanitarian response design and implementation; and Assess overall programme and draw technical, market, and methodological implications for the design of future humanitarian responses and their contribution to resilience building. This Discussion Paper provides considerable detail on which facets of the implementation of FIRP were successful and where implementation fell short in addressing the needs of the affected population, in ensuring that Malawi was better prepared for future food crises, and in laying a foundation for improved resilience in the face of such shocks for both the affected households and Malawi as a whole. The 2016/17 FIRP was largely successful in preventing disaster and saving lives and livelihoods. However, the assessment of the design and implementation of the FIRP highlighted the high level of dependency of the Malawi government on its development partners for resources to undertake such humanitarian responses and the significant deficiencies in the technical and institutional capacity of the institutions responsible for responding. Unless the cycle of food insecurity is broken and the resilience of Malawian food systems increased, the government of Malawi and its development partners will continue to depend on FIRP-type interventions to save people’s lives and protect them from food insecurity and hunger.